2012
DOI: 10.1109/tbme.2012.2202661
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Cardiac Bidomain Simulations Using Graphics Processing Units

Abstract: Anatomically realistic and biophysically detailed multiscale computer models of the heart are playing an increasingly important role in advancing our understanding of integrated cardiac function in health and disease. Such detailed simulations, however, are computationally vastly demanding, which is a limiting factor for a wider adoption of in-silico modeling. While current trends in high-performance computing (HPC) hardware promise to alleviate this problem, exploiting the potential of such architectures rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 30 publications
0
63
0
1
Order By: Relevance
“…To validate the performance of the standard and optimized accumulation algorithms we solve an elliptic PDE, discretized with linear tetrahedral finite elements, that describes the electric potential on the rabbit heart [13,14] shown in Fig. 5, with a parallel conjugate gradient algorithm with algebraic multigrid preconditioner (PCG-AMG).…”
Section: Benchmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the performance of the standard and optimized accumulation algorithms we solve an elliptic PDE, discretized with linear tetrahedral finite elements, that describes the electric potential on the rabbit heart [13,14] shown in Fig. 5, with a parallel conjugate gradient algorithm with algebraic multigrid preconditioner (PCG-AMG).…”
Section: Benchmarkmentioning
confidence: 99%
“…5. For more details on the original problem setting and its solution we refer the reader to [13,14].…”
Section: Benchmarkmentioning
confidence: 99%
“…Applications of this approach in biomedical simulations can be found in [4], [5]. We only consider parallel storage schemes for vectors and matrices that are data consistent on each processor, i.e., if any element is on more than one processor, the value is the same on all processors.…”
Section: Parallel Data Distributionmentioning
confidence: 99%
“…However, with unstructured three dimensional (3D) bidomain simulations, the number of iterations required for convergence became prohibitive. In a more recent work Neic et al [26] showed that 25 processors were equivalent to a single GPU when computing the bidomain equations. This new capability to solve the governing equations on a relatively small GPU cluster makes it possible to one day introduce simulation using patient specific computer models into a clinical workflow.…”
Section: Introductionmentioning
confidence: 99%